If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7(18-x)-6(3-5x)=-(7x+9)-3(2x+5)=12
We move all terms to the left:
7(18-x)-6(3-5x)-(-(7x+9)-3(2x+5))=0
We add all the numbers together, and all the variables
7(-1x+18)-6(-5x+3)-(-(7x+9)-3(2x+5))=0
We multiply parentheses
-7x+30x-(-(7x+9)-3(2x+5))+126-18=0
We calculate terms in parentheses: -(-(7x+9)-3(2x+5)), so:We add all the numbers together, and all the variables
-(7x+9)-3(2x+5)
We multiply parentheses
-(7x+9)-6x-15
We get rid of parentheses
-7x-6x-9-15
We add all the numbers together, and all the variables
-13x-24
Back to the equation:
-(-13x-24)
23x-(-13x-24)+108=0
We get rid of parentheses
23x+13x+24+108=0
We add all the numbers together, and all the variables
36x+132=0
We move all terms containing x to the left, all other terms to the right
36x=-132
x=-132/36
x=-3+2/3
| (2x^2+5x)^2-10x-25x=14 | | 10x-4=8-6x | | 905=72;r=7 | | 7-5(3x-4)=3-(2x+5)-12 | | 7-5(3x-4)=-(2x+5)-12 | | 2/7y-1/7=5/7y+2/7 | | 13m-2=9m-6 | | 2x-5x+3-3-2-7=0 | | 26-11x=10+5x | | 17+5v=62 | | 2x-(5x+3)-7+(3x-2)=0 | | 13+3u=46 | | 8-3.2v=1.6 | | 4u+4.7=1.9 | | 2x=4x+40 | | 0.11+0.01y=0.22+y | | 5+3x-x+7=29 | | 4(3-x)=5x | | x−43=−2 | | 13=1/2(9x-6) | | 7w=10=-4 | | (11k^2+33k)÷(k+3)=0 | | 5y-7=3y-7 | | v/5-11=8 | | 4y+11=55 | | 0.6x+0.5=0.14 | | 0.6x+0.5= | | 2y+15=48 | | 132÷3√2=2n | | 3=3.3/x | | -0.75z-0.8z=0.05 | | (3t+2)^2-(2t−5)^2=0 |